6
$\begingroup$

I stuck to do this,

$$\lim_{n\to \infty} \frac{1+2^2+\ldots+n^n}{n^n}=1.$$

The only thing I have observed is $$ 1\le \lim_{n\to \infty} \frac{1+2^2+\ldots+n^n}{n^n}$$ I am unable to get its upper estimate so that I can apply Sandwich's lemma.

$\endgroup$
  • $\begingroup$ Cesaro-Stolz should do the trick $\endgroup$ – Simply Beautiful Art Sep 11 '17 at 20:43
11
$\begingroup$

$$1\le \frac{1+2^2+\ldots+n^n}{n^n}\le \frac{n+n^2+\ldots+n^n}{n^n} = \frac{n\frac{n^n-1}{n-1}}{n^n} = \frac{n^{n+1}-n}{n^{n+1}-n^n}\xrightarrow{n\to\infty} 1$$

$\endgroup$
  • $\begingroup$ Why $ \frac{n^{n+1}-n}{n^{n+1}-n^n}\xrightarrow{n\to\infty} 1$? $\endgroup$ – Sachchidanand Prasad Sep 11 '17 at 21:01
  • 1
    $\begingroup$ @SachchidanandPrasad Try dividing each term in the entire fraction by the highest degree term - in this case $n^{n+1}$. It should follow without much pain from there. $\endgroup$ – Ducky Sep 11 '17 at 21:03
  • $\begingroup$ Okay okay, sorry it was easy. Thanks $\endgroup$ – Sachchidanand Prasad Sep 11 '17 at 21:04
  • $\begingroup$ It might be clearer to end with $${n{n^n-1\over n-1}\over n^n}=\left(n\over n-1\right)\left(1-{1\over n^n}\right)\to1$$ $\endgroup$ – Barry Cipra Sep 12 '17 at 2:29
3
$\begingroup$

Consider any sequence $a_n$ with the property that $\lim\limits_{n\to\infty}a_n=\infty$ and $\lim\limits_{n\to\infty}\frac{a_{n-1}}{a_n}=0$. It follows by Stolz–Cesàro that

$$\lim_{n\to\infty}\frac{a_1+a_2+\dots+a_n}{a_n}=\lim_{n\to\infty}\frac{a_n}{a_n-a_{n-1}}=\lim_{n\to\infty}\frac1{1-\frac{a_{n-1}}{a_n}}=1$$

Here, we have $a_n=n^n$.

$\endgroup$
1
$\begingroup$

$$1+2^2+3^3+\cdots(n-2)^{n-2}+(n-1)^{n-1}+n^n<\\n^{n-2}+n^{n-2}+n^{n-2}+\cdots n^{n-2}+n^{n-1}+n^n.$$

When divided by $n^n$, these terms are bounded by $\dfrac n{n^2}+\dfrac1n+1$.

$\endgroup$
1
$\begingroup$

$$\lim_{n \rightarrow \infty} \frac{1^1 + 2^2 + \dots + (n-1)^{n-1} + n^n}{n^n} = \lim_{n \rightarrow \infty} \left(\frac{1^1}{n^n} + \frac{2^2}{n^n} + \dots + \frac{(n-1)^{n-1}}{n^n} + 1 \right) $$

Let's examine that second to last term:

$$ \begin{align} \lim_{n \rightarrow \infty} \frac{(n-1)^{n-1}}{n^n} &= \lim_{n \rightarrow \infty} \frac{1}{n}\frac{(n-1)^{n-1}}{n^{n-1}} \\ &= \lim_{n \rightarrow \infty} \frac{1}{n} \left( \frac{n-1}{n} \right)^{n-1}< \lim_{n \rightarrow \infty} \frac{1}{n} \cdot 1\\ &= 0 \end{align}$$ The second largest term is zero, none of the terms are negative, the sum is 1: $$\lim_{n \rightarrow \infty} \frac{\sum\limits_{m=1}^{n} m^m}{n^n} = 1$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.